Guidance procedures in high school : some recommended procedures based upon a survey of present practices in Minnesota - Wrenn, C. Gilbert (Charles Gilbert), 1902-2001 (Modern school practices series, 1950)
Guidance Procedures in High School was first published in 1950. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. This volume is number 1 in the Modern School Practices series; established in 1950 by the College of Education at the University of Minnesota, and the Bureau of Educational Research. The series is designed as a replacement to two earlier series: the Series on Individualization of Instruction and the Modern School Curriculum series. This monograp.